Hubungan Hasil Belajar dengan Kemampuan Argumentasi Ilmiah Peserta Didik SMAN 1 Payakumbuh pada Materi Sistem Imun - Tasya Amelia; Muhyiatul Fadilah; Helendra Helendra; Elsa Yuniarti (ISLAMIKA, 2023)
Learning outcomes are an assessment of the abilities possessed by students after participating in the learning process. Low learning outcomes caused by low scientific argumentation. This study aims to determine the relationship between learning outcomes and the ability of scientific argumentation of students of SMAN 1 Payakumbuh on the immune system material. This research is a descriptive study with the correlation method. The research sample consisted of 34 students of class XII MIPA 8 SMAN 1 Payakumbuh. . The research instrument is in the form of valid student learning outcomes tests and scientific argumentation ability tests. The results showed that students' learning outcomes were in the moderate category with an average of 63% and students' scientific argumentation abilities were included in the weak category with an average of 39.02%. There is a positive and significant correlation between learning outcomes and the scientific argumentation abilities of class XII MIPA 8 students in the immune system material with a value of r = 0,658 which is in the very strong category. The value coefficient = 6,562 is greater than the coefficient =2,0369. So it can be concluded that there is a positive and significant relationship between learning outcomes and scientific argumentation abilities of SMAN 1 Payakumbuh students on the immune system material.